THE EFFECT OF RESILIENCE ON BURNOUT AMONG THE BLUE COLLARED EMPLOYEES IN METAL FACTORIES - K.RAJAN SANTHOSH and JIMMY JAMES (EXCEL International Journal of Multidisciplinary Management Studies, 2013)
Resilient individuals are able to turn stressful events into opportunities for personal growth and benefit, exploiting the chances in ever great challenges. A resilient workforce is healthy, energetic, durable, and enthusiastic with fast, friendly, flexible, and focused workers in it. The present study enquires if burnout, in the blue collared employees in metal factories, has a significant inverse relationship with resilience. Sample included 40 blue collared employees from Sree Narayana Engineering Industries, Shoranur-2, Palakkad District in the state of Kerala, India. Resilience of the participants was measured using BU resilience scale (Annalakshmi, 2009). Maslach burnout inventory (Maslach & Jackson, 1981) was used to measure their burn out. Correlation analysis indicated that resilience had a strong and significant inverse relationship with burnout. Regression analysis indicated that resilience in the employees can predict a reduction of burn out. Among the four factors of burn out, reduced personal accomplishments indicated a high negative relationship with resilience. Implications and recommendations for the future research were discussed.